TRANSFER TO THE LONG POURING OF STEEL AT MNLZ-1,2, RUP «BMZ» - I. I. Shkulkova; A. K. Turygin (Литьë и металлургия)
The transfer to long pouring of steels with use of CNC of firm VESUVIUS (Germany) is carried out on machines of continuous casting of slugs No1, 2 of RUP «BMZ».